Specificity of long-term unemployment risk among creative economy workers - Monika Wojdyło-Preisner; Kamil Zawadzki (Comparative Economic Research. Central and Eastern Europe, 2015)
This paper investigates the determinants of long-term unemployment in Poland for workers in the creative economy. Over 2,100 unemployed artists, journalists, architects, designers, craftspeople and creative industry technicians registered in public employment agencies are examined to discover the relationship between the probability of long-term unemployment and basic socio-demographic variables, human capital characteristics, as well as type of the local labour market. The outcomes based on the sample of creative workers are compared to a study of almost 44,000 registered unemployed representing all professions. Results indicate that such characteristics as: male gender, age under 30, married, first unemployed registration within the last three years, extensive work experience, high qualifications and multi-skilling each considerably decrease the likelihood of being unemployed for more than 365 days, both among creative workers and among all unemployed. The strength of this influence, however, differs within these two groups, with some co-variates significantly affecting the likelihood of long-term unemployment in the general sample. For example health, having children, or a willingness to take any job all appear to be non-significant for creative workers.
Keywords: 330; Creative economy workers; Long-term unemployment determinants; Labour market policy